Meningkatkan Kualitas Produk Panel Box App-Tl Aluminium dengan Efisiensi Biaya Kualitas Menggunakan Metode Continuous Improvement di PT Powerindo Prima Perkasa - Daniel Hamonangan Sinaga; Prihantoro Syahdu Sutopo (Syntax Corporation Indonesia, 2024)
Nowadays, industrial competition in an era of globalization in manufacturing can improve the quality of the products produced. PT. Powerindo Prima Perkasa is a metal and electrical equipment company. Because of the Make To Order (MTO) production process, there is often a decline in quality. The objective of the research is to find factors that cause rework, identify the cost of poor quality (COPQ) and the application of Plan, Do, Check and Action (PDCA). Data taken from May to October 2023 with an average rework cost and COPQ of Rp 6.478.871. There were 6 points of finding defects with a total of 2,455 defects. The rework problem diagram shows the two highest points of finding thin powder and scratch. Through the PDCA application, data is taken from the previous rework cause analysis diagram. Plan level, there are four improvement factors: man, method, machine, environment. Stage do, applying improvements is training, new methods, new way of working machines with waste powder 25%, monitoring new layout. Obtained 748 defects with average cost of rework and COPQ after simulation of Rp 4.832.053. The action phase followed up on the previous phase by providing standardization through training periodically at least once in 3 months, performing monitoring every day. Next, follow up improvements with PDCA through the problem diagram after the highest simulation is the aluminum plate gap defect.